(untitled) (مجلة إحالات, 2026)
This intervention seeks to trace the theme of death in the novel "Ramadan Nights" by the Algerian Wassini Al-Araj; as a constructive topic, through which the writer established his story, as he relied on living reality at his moment when the pandemic / Corona pandemic/epidemic spread, so the writer conveyed to us in the form of My narrative of the negatives of quarantine, and the consequences of the pandemic, through which he revealed the fragility of families and the fragility of relationships, in addition to his talk about the unspoken within society. Based on this, the following problematic entry is raised: How did the topic of the pandemic form a constructive topic in the contemporary Algerian novel? And in the novel Liliat Ramada And how did the writer employ it? And why? How did the theme of death appear in the novel Ramada Nights? And how did the writer invest the topic of the pandemic in addressing his idea? To other questions that arise from each other.